Strategi Peremajaan Sawit Rakyat dan Pengembangan Usaha KUD Sumber Makmur Menggunakan Pendekatan Business Model Canvas - Siahaan, Herlyna Novasari; Hasibuan, M. Fariz Afif; Nofitasari, Rahmi; Putra, Hendris Syah (Universitas Galuh, 2024)
KUD Sumber Makmur is one of the Village Unit Cooperatives located in Pelalawan Regency, Riau. As a form of sustainable palm oil management, cooperative members' oil palm lands that have reached economic maturity need to be replanted. Apart from that, managing KUD cooperatives requires a cooperative business development strategy model. This research aims to identify strategies for rejuvenating smallholder palm oil and business development for KUD Sumber Makmur using the Business Model Canvas approach. The research was conducted in September 2023 at KUD Sumber Makmur, Pelalawan Regency, Riau. The data collection methods in this research are primary data and secondary data. The data analysis used in this research uses a qualitative descriptive type. The strategy for rejuvenating smallholder oil palms at KUD Sumber Makmur consists of the data collection stage and the implementation stage of the smallholder oil palm rejuvenation program. The business development strategy at KUD Sumber Makmur is: The Key Partner of the cooperative is PT Asian Agri, Key Activities of the cooperative consist of a savings and loan unit, agricultural production facilities unit, FFB Transportation unit, and FFB Sales unit, Value Proposition consists of cooperative FFB Quality and Palm Oil Certification, Customer relationships consist of efforts to maintain the quality of FFB and establish good communication with offtakers. Customer segments consist of off-taker companies (PT Asian Agri) and BPDPKS. Key resources consist of partner farmers' land, cooperative buildings, and transportation equipment. Channels consist of Direct and Contract methods, Cost Structure consists of production costs and operational costs, Revenue streams consist of FFB Sales